UJI KUAT TEKAN BATA BETON UNTUK PASANGAN DINDING DENGAN CAMPURAN LIMBAH STYROFOAM (EXPANDED POLYSTYRENE) - Ega Rismana (Menara: Jurnal Teknik Sipil, 2022)
Based on statistics on the amount of waste in DKI Jakarta, until plastic is in the third rank after organic waste and paper. In this study, the dimensions, bulk weight, flexural strength and compressive strength of concrete bricks for wall pairs will be tested. The main materials for making concrete bricks are cement, fine aggregate and water. Styrofoam waste will be used as a substitute for fine aggregate with variations in the percentages used, namely 0%, 10%, 20% and 30%. Using the test object in the form of a beam with a length of 390 mm, a width of 90 mm and a thickness of 100 mm. Water cement factor 0.4. Testing the test object at the age of 28 days. Dimensional test results on all variations have met the requirements. The average compressive strength of concrete bricks with variations of 0%, 10%, 20% and 30% styrofoam mixture at the age of 28 days, respectively, is 74,87 kg/cm2, 42,28 kg/cm2, 44,28 kg/ cm2 and 35,45 kg/cm2. The average flexural strength of concrete bricks with variations of 0%, 10%, 20% and 30% styrofoam mixtures at the age of 28 days, respectively, is 1,204 N/mm2, 0,473 N/mm2, 0,705 N/mm2 and 0,962 N/mm2.